Studies of True Bugs of Xinjiang, Western China. II. Cimicomorpha: Lace Bugs (Hemiptera: Heteroptera: Tingidae: Tinginae) - Golub, Victor B.; Luo, Zhaohui; Vinokurov, Nikolai N. (Zootaxa, 2012)
34 species from 12 genera of lace bugs occur in the fauna of Western China; of them, 11 and 10 species are recorded for the first time from China and Xinjiang, respectively. Kalama wangi sp. n. is described. Kalama aridula (Jakovlev, 1902) is closely related to K. tricornis (Schrank, 1801), and is restored as a good species; morphological differences between these two species are discussed. A key to Central Asian species of the genus Catoplatus Spinola, 1837 is constructed.